A Case Study On Liner Division Of Malaysia Shipping Line (MSL) Berhad. - Abdul Aziz, Azlan (2000)
This paper ascertains the viability of MSL's Liner Division in the shipping trade. For number of years, the liner shipping industries is operating in a difficult market. Prospects for an improvement are rather remote.